Gaya dan Model Klasik Kepemimpinan dalam Pendidikan Islam: Demokratis dan Otoriter, Kharismatik dan Laissez-Faire - Muh. Sulaiman Rifai Aprianus Mukin; Tobroni; Abdul Haris (Fakultas Agama Islam Universitas Billfath, 2024)
This study aims to provide an in-depth insight into leadership styles and models in Islamic education, and to analyze the application of various leadership styles such as democratic, authoritarian, charismatic, and laissez-faire in Islamic educational institutions. The research methodology employed was a Systematic Literature Review, gathering and analyzing data from books, journals, articles, and other relevant literature sources. The findings indicate that the democratic leadership style is preferred in Islamic education for its support of consultation and participation. Conversely, the authoritarian style is often applied in traditional Islamic boarding schools to maintain discipline. Charismatic leadership can enhance morale and commitment but carries the risk of dependency on a single figure. The laissez-faire style is rarely applied due to its potential for lack of direction and control. The study suggests that a combination of various leadership styles can create an effective and harmonious educational environment.